Growth and Characterization of Anthranilic acid Crystals - Dinagaran, S.; Srinivasan, P; Srinivasan, P; Vijayakumar, S; Vijayakumar, S; Balaji, J; Balaji, J (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
ABSTRACT Single crystals of Anthranilic acid (AA) have been successfully grown and purity of materials has been increased by repeated recrystallization process. Single crystals have been grown by slow evaporation technique. The grown crystal was characterized by Single crystal X-Ray diffraction, Powder XRD, FTIR, UV-Vis, DTA/TGA, Dielectric studies and SHG respectively. The observed results from various characterization show the suitability of NLO application. The second harmonic generation of the grown crystal was checked using Kurtz and Perry technique. Thermal stability and melting point of the grown crystal were found by thermal analysis. The Physical strength of the grown AA crystal was measured from Vickerâ€™s hardness test.Â 